Using Web-Services to Manage and Control Access to Multimedia Content - Serrão, C.; Dias, J.; Delgado, J. (ISWS'05- The 2005 International Symposium on Web Services and Applications, Las Vegas, Nevada, USA, 2005)
In a vastly interconnected World, the WebServices (WS) computing paradigm is gaining momentum. Most Web Services applications existing today are being developed in the E-Business or E-Commerce context, mainly for Enterprise Application Integration (EAI) [12]. This paper describes a distributed architecture that largely uses WS technology to control and manage the access to multimedia content and that represents the new and emerging market of Digital Rights Management (DRM). This architecture deploys some critical DRM elements in a service-oriented architecture, such as device and user identification and authentication, content registration and protection, license representation and production and payment. This paper presents the conceptual architecture referred to as OpenSDRM [3], and provides some technical details about its development and deployment.